Statement Simplification

Variable definition :

Simplification :


2x+(p+2)y=2(p-1)x+2y=1

// Connecting 2x+(p+2)y=2 and (p-1)x+2y=1 using shared item y
2x+(p+2)1+(-p+1)x2=2(p-1)x+2y=1
// There is (p+2)(1+(-p+1)x)2 item in expression 2x+(p+2)(1+(-p+1)x)2 , so i put it in from of the expression.Result is
4x+(p+2)(1+(-p+1)x)2=2(p-1)x+2y=1
// Decomposition of summation 1+(-p+1)x in item (p+2)(1+(-p+1)x) .Result is 4x+p1+p(-p+1)x+2+2(-p+1)x Theory
4x+p1+p(-p+1)x+2+2(-p+1)x2=2(p-1)x+2y=1
// Put of item x from expression 4x+p+p(-p+1)x+2+2(-p+1)x
x(p(-p+1)+4)+p+2+2(-p+1)x2=2(p-1)x+2y=1
// Put of item x from expression x(p(-p+1)+4)+p+2+2(-p+1)x
x(2(-p+1)+p(-p+1)+4)+p+22=2(p-1)x+2y=1
// Decomposition of summation -p+1 in item 2(-p+1) .Result is p(-p+1)+4-2p+2 Theory
x(p(-p+1)+4-2p+2)+p+22=2(p-1)x+2y=1
// Multiplication of numbers 2 * -1 = -2
// Count of numbers 4 + 2 = 6
x(p(-p+1)+6-2p)+p+22=2(p-1)x+2y=1
// Decomposition of summation -p+1 in item p(-p+1) .Result is 6-2p-pp+p1 Theory
x(6-2p-pp+p1)+p+22=2(p-1)x+2y=1
// Put of item p from multiplication -pp
x(6-2p-p2+p1)+p+22=2(p-1)x+2y=1
// Put of item p from expression 6-2p-p2+p
x(6+p(1-2)-p2)+p+22=2(p-1)x+2y=1
// Count of numbers 1 + -2 = -1
x(6-p-p2)+p+22=2(p-1)x+2y=1
// Decomposition of quadratic -p2-p+6 , looking for roots for p
// Diskriminant is 25
// Solutions are 2 and -3
// Roots are p-2 and p+3
-x((p-2)(p+3))+p+22=2(p-1)x+2y=1
x(-p+2)(p+3)+p+22=2(p-1)x+2y=1
// I express x from equation x(-p+2)(p+3)+p+22=2
x=4-p-2(2-p)(p+3)(p-1)x+2y=1
// Count of numbers 4 + -2 = 2
(x=2-p(2-p)(p+3)2-p02-p=04-p-2=0)(p-1)x+2y=1
// Count of numbers 4 + -2 = 2
(x=2-p(2-p)(p+3)2-p02-p=02-p=0)(p-1)x+2y=1
// Canceling out 2-p in 2-p(2-p)(p+3)
(x=1(p+3)2-p02-p=02-p=0)(p-1)x+2y=1
// Decomposition of item x=1(p+3)2-p02-p=02-p=0 in statement (x=1(p+3)2-p02-p=02-p=0)(p-1)x+2y=1 .
(p-1)x+2y=1x=1(p+3)2-p0(p-1)x+2y=12-p=02-p=0
// Transport items not containing p to the right in equation 2-p0
// Multiplication of p-2 with -1
(p-1)x+2y=1x=1(p+3)p2(p-1)x+2y=12-p=02-p=0
// Transport items not containing p to the right in equation 2-p=0
// Multiplication of p=-2 with -1
// Transport items not containing p to the right in equation 2-p=0
// Multiplication of p=-2 with -1
(p-1)x+2y=1x=1(p+3)p2(p-1)x+2y=1p=2p=2
(p-1)x+2y=1x=1(p+3)p2(p-1)x+2y=1p=2
// Connecting (p-1)x+2y=1 and x=1(p+3) using shared item x
// Connecting (p-1)x+2y=1 and p=2 using shared item p
p-1p+3+2y=1x=1(p+3)p2(2-1)x+2y=1p=2
// Count of numbers 2 + -1 = 1
p-1p+3+2y=1x=1(p+3)p21x+2y=1p=2
// There is p-1p+3 item in expression p-1p+3+2y , so i put it in from of the expression.Result is
p-1+(p+3)2yp+3=1x=1(p+3)p2x+2y=1p=2
// I express y from equation (p+3)2y+p-1p+3=1
y=1(p+3)-p+12(p+3)x=1(p+3)p2x+2y=1p=2
// Count of numbers 1 + 3 = 4
x=1(p+3)p2y=-p+4+p2(p+3)p+30x+2y=1p=2
// Put of item p from expression -p+4+p
x=1(p+3)p2y=p(1-1)+42(p+3)p+30x+2y=1p=2
// Count of numbers 1 + -1 = 0
x=1(p+3)p2y=p0+42(p+3)p+30x+2y=1p=2
// Count of numbers 0 + 4 = 4
x=1(p+3)p2y=42(p+3)p+30x+2y=1p=2
// Put of item 2 from multiplication 22(p+3)2
2(2-1)p+3
x=1(p+3)p2y=2(2-1)p+3p+30x+2y=1p=2
// Count of numbers 2 + -1 = 1
x=1(p+3)p2y=21p+3p+30x+2y=1p=2
// Transport items not containing p to the right in equation p+30
x=1(p+3)p2y=2p+3p-3x+2y=1p=2

Result: x=1(p+3)p2y=2p+3p-3x+2y=1p=2